Using the Health Belief Model to Understand Pesticide Use Decisions (The Pakistan Development Review, 2010)
Farmers use pesticide to protect their crops from pests which in-turn help them maximise agricultural output on limited acres of land. However, the extensive use of such pesticide results in substantial health and environmental threats. According to WHO (1990) pesticide use causes 3.5 to 5 million acute poisonings a year. Rough estimates show that 20,000 workers dying from exposure every year and most of them from developing countries. The literature shows that health and environmental hazards of pesticide use occur due to lack of information, awareness and knowledge which are chief contributing factors of extensive overuse or misuse of hazardous pesticide and dangerous practices [Forget (1991); Dasgupta, et al. (2005a); Ibitayo (2006)]. Research has also shown that health and environmental hazards of pesticides can be avoided by awareness, education and changing farmer’s attitude and behaviour regarding pesticide use [Dasgupta, et al. (2005a)]. Therefore, the first step in developing pesticide’s health and environmental hazard reduction policy is to set up the extent of the problem by investigating farmer’s attitudes and behaviours regarding pesticide use [Koh and Jeyaratnam (1996); Dasgupta (2005a, 2005b)]. Such information is critical to identify the ‘prospects and constraints to the adoption of alternative crop protection policy’ [Ajayi (2000)].